Cyana ebigane, a new species from Gabon (Lepidoptera: Erebidae: Arctiinae) - Volynkin, Anton V.; Karisch, Timm; Durante, Antonio (Zootaxa, 2021)
A new species of the genus Cyana Walker, 1854, Cyana ebigane sp. n. is described from Gabon. The new species belongs to the subgenus Strigivulpecula Karisch, 2013 and comparisons are made with its congeners C. nemasisha Roesler, 1990, C. rufeola Karisch & Dall’Asta, 2010, C. klausruedigerbecki Karisch, 2005 and C. fasciata Karisch, 2013. Cyana nemasisha Roesler, 1990 is reported from Gabon for the first time. Adults and male genitalia of the new and the similar species discussed in the paper are illustrated.